Creative Economy: The Influence of Service Quality, Product Quality, Store Atmosphere, and Social Media on Culinary Consumer Satisfaction in Garut Raya - Agnia Fadillah; Jeni Susyanti; Dwiyani Sudaryanti (MEC-J (Management and Economics Journal), 2023)
Food and beverage consumption is the largest component of household consumption in Garut. This condition is an opportunity for culinary businesses to create competitive advantage, product quality, and store atmosphere as an effort to increase consumer satisfaction. Technological developments encourage people to use social media to socialize and seek information. Social media influencers are the most effective way to promote a culinary business. This study aims to determine and analyze the effect of service quality, product quality, and store atmosphere on consumer satisfaction through social media influencers in the culinary subsector in Garut Raya. This type of research uses cause and effect. The research population is not known with certainty, the sampling technique uses the Chocran formula with a total sample of 97 respondents. The data source is primary data with data collection techniques using questionnaires. Data analysis using Structural Equation Model Partial Least Square (SEM-PLS). The results of this study indicate service quality, product quality, and social media influencers have a significant positive effect on customer satisfaction, while store atmosphere has no effect. Service quality and product quality have no significant effect on social media influencers, while store atmosphere has an effect. Service quality and product quality have no effect, while store atmosphere has an effect on consumer satisfaction through social media influencers